Nigerian Children’s Right to be Left Alone on the Metaverse: A Comparative Analysis - Ehirim, Nwanneka Flora; Ehirim, Ugochukwu (Universitas Negeri Gorontalo, 2026)
In General Comment 25 (2021), the liberties of children within the metaverse were fortified, protected and upheld. A sound legislative foundation is indispensable to this end. This article evaluates the scope of children’s privacy rights and liberties to have their personal data protected under the Nigerian legal system. The analysis also extends to legislative frameworks in the EU, South Africa and USA, where provisions for child privacy protection and safeguards against online abuses are more comprehensive. The doctrinal approach of juridical research is adopted in this article, facilitating robust analysis of the diverse municipal, regional and transnational regulatory regimes as applicable to Nigeria, and by extension, South Africa. It is demonstrated that, whereas both nations have achieved significant milestones by legislation of children’s liberties anywhere, including the metaverse, their legal frameworks have not sufficiently safeguarded these freedoms, particularly with respect to privacy on digital ecosystem. The case was made that inadequate, imprecise regulation may undermine effective nurturing of children when their privacy is undermined, particularly within the digital space, by way of chilling effect. Consequently, reform of the relevant legal provisions is imperative for Nigeria, with a clear suggestion for children to be consulted and their opinions respected throughout the legal reformation process, since they hold a statutory entitlement to engagement on issues affecting them.